A mathematical model of predicting residual moment capacity of RC elements after fire exposure. (13th March 2017) - , Rajkishor; Bhargava, Pradeep; Bhandari, Navratan M.; Sharma, Umesh K.
Abstract : Purpose: This paper aims to present a mathematical model of predicting the residual moment capacity of fire-damaged reinforced concrete (RC) elements after cooling to ambient temperature which also reflects the role of bond between steel rebar and surrounding concrete. Design/methodology/approach: The prediction of residual moment capacity of fire-damaged RC element has been carried out for two scenarios: by assuming perfect bond between surrounding concrete and steel rebar after fire exposure and by incorporating a relative slip between surrounding concrete and steel rebar and hence assuming partial bond between them after fire scenario. The predicted results are then compared with the experimental results available in different literatures. Findings: It is found that on comparison between the predicted results and the experimental results, the proposed mathematical prediction model, when bond-characteristics are considered, shows better agreement with the experimental results as compared with those by conventional method with perfect bond assumption. Originality/value: The constitutive relationship for thermal residual properties of steel rebar and concrete has been used in the proposed prediction model along with relative slip approach between surrounding concrete and steel rebar after fire scenario and consequently to predict the residual moment capacity of the fire-damaged RC element after cooling.